INTRACEREBRAL HEMORRHAGE AND THE USE OF VARIOUS TYPES OF ANTICOAGULANTS – CLINICAL PRESENTATION AND TREATMENT OUTCOMES - Dimitrijević, Ljubica; Munjiza, Dejan; Mitović, Nikola; Stanković, Marija S.; Georgievski-Brkić, Biljana; Vukićević, Marjana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Anticoagulant therapy plays a key role in the prevention and treatment of various vascular diseases, but it simultaneously increases the risk of hemorrhagic complications, including intracerebral hemorrhage (ICH). This study aimed to examine the outcomes of patients with ICH based on prior anticoagulant therapy. Methods: This was a retrospective cohort study involving 37 out of 277 patients with ICH from the hospital registry treated between January and November 2024 at the Special Hospital for Cerebrovascular Diseases "Sveti Sava". All patients were divided into two groups: those treated with vitamin K antagonists (VKA) or direct oral anticoagulants (NOAC). The treatment outcome of patients at discharge and 90 days after discharge was determined using the modified Rankin Scale (mRS).Results: In the group of patients previously treated with VKA, the mean mRS score at discharge was 4.6 ± 1.8, while in the group previously treated with NOAC therapy, it was 5.1 ± 1.7, with no statistically significant difference between the groups (p = 0.442). Additionally, no statistical significance was found in the mRS 90 days after discharge (p = 0.341). In the VKA-ICH group, the mean value was 4.3 ± 2.2, while in the other group, it was 4.9 ± 2. In the first group, the mortality rate was 58%, while in the second group, it was 76%.Conclusion: Patients with ICH and prior VKA therapy showed no significant differences in treatment outcomes compared to patients with prior NOAC therapy.
Keywords: intracerebral hemorrhage; vitamin K antagonists; direct oral anticoagulants